Brightness of the Night Sky Affects Loggerhead (Caretta caretta) Sea Turtle Hatchling Misorientation but Not Nest Site Selection - Stanley, Thomas R.; White, Jeremy M.; Teel, Susan; Nicholas, Mark (Frontiers in Marine Science, 2020)
Sea turtles in the Gulf of Mexico, which are listed as either threatened or endangered under the US Endangered Species Act, face numerous threats but are particularly susceptible to the negative effects of light pollution on nesting beaches. Light pollution affects the distribution, density, and placement of nests on beaches, and disrupts seafinding in hatchlings emerging from nests; often leading to their death. Rapid urban growth near Gulf Islands National Seashore (GUIS), Florida, USA, over the last century has contributed to increased light pollution on its beaches. There is concern that light pollution is causing females to lay nests in at-risk locations subject to erosion and flooding, and is causing the observed high rates of hatchling misorientation. From 2015-2016, we measured brightness of the night sky, horizon profile, and lunar variables at GUIS at loggerhead (Caretta caretta) nests to assess the effects of brightness on laying of at-risk nests and hatchling misorientation. In addition, we quantified the effects of relocating at-risk nests on nest success. We found that contrast in brightness between the landward and seaward directions at GUIS was partially responsible for high rates of hatchling misorientation, and there was a strong moderating influence of lunar fraction and lunar altitude on hatchling misorientation: larger lunar fractions and lower lunar altitudes reduced misorientation. We did not document an effect of artificial light, horizon profile, or lunar fraction on the propensity of loggerheads to lay nests in at-risk locations, and found no evidence that relocating nests at GUIS reduced loggerhead nest success. Rather, we found nest success was improved and hatchling misorientation rates were reduced for relocated loggerhead nests.